Intellectual Property Rights and Computer Applications for Pharmaceutical Research and Development - Bhattacharya, Sankha; Saindane, Dnyanesh (Applied Drug Research, Clinical Trials and Regulatory Affairs, 2021)
Intellectual Property Rights (IPR) are intellectual privileges that allow authors and inventors to defend their original inventions from misuse or theft. With the assistance of algorithms, clinical science has taken on a different level in recent years. Various advanced tools can be used to investigate pharmacokinetics profiling, in silico experiments, receptor simulations, drug synergistic effects, and so on. Computational scientists are making continuous efforts to figure out how to connect business models in pharmacology. However, software theft and security rights remain major concerns for all. In order to avoid such violations, IPR compliance for R as well as promoting machine applications is critical. This compilation will illustrate diverse software concepts, the latest patent data structures, copyright management laws for software, trade secrets, compliance rights, software patenting and contracts, artificial technology priorities and problems, licenses, and case studies relating to IPR violations in pharmaceutical and other fields.
Keywords: artificial intelligence